Ethnomathematics of fish catching exploration in Musi River. (October 2020) - Malalina, M; Putri, R I I; Zulkardi, Z; Hartono, Y
Abstract: The activities of the people catching fish at the bottom of the Musi River contain cultural elements which indirectly contain mathematical concepts. So far, fishing activity has only been seen from the economic aspect but not from the cultural concept associated with mathematics. So that the formulation of the problem in this research is to identify the ethnomathematic aspects of fishing activities in the Musi River. The method used in this research is descriptive qualitative. The data obtained were then analyzed by using ethnomathematic aspects according to Alan J. Bishop. Data collection was carried out by field studies, interviews and documentation. Sources of data in this research were 10 peoples who directly catch fish in the Musi River. The results of the research can be concluded that there are ethnomathematic aspects of fishing activity in the Musi River, namely determining the location, measuring, and designing. Thus ethnomathematics in the Musi River can be used in junior high school mathematics learning, namely in the material of cartesian coordinates, sets, social arithmetic, velocity, distance, and geometry.